TRANSITION SIGNALS IN HEADLINE NEWS - Sari, Indah (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
This study aimed to analyze the types of transition signals in headline news and the reasons for using transition signals in writing. This study applied a descriptive qualitative design. The sources of the data were three headline news taken from Antaranews.com entitled “Indonesia urges ASEAN, China to help maintain regional stability,” the jakartapost.com entitled “Myanmar to dominate ASEAN agenda, but little progress expected”, and 9News.com entitled “Russian President Vladimir Putin won't attend upcoming G20 summit in Bali” published on November 11th, 2022. The technique of data collection was documentation and the procedures in the the data analysis were 1) reading the headline news, 2) finding the transition signal in headline news, 3) underlining the transition signals in headlines news, 4) classifying the transition signals, 5) counting the total frequencies of transition signals, and 6) finding the reasons of using transition signals in writing. The results showed that the types of transition signals found in the headline news were to indicate addition, time, sample, distinction, and cause and effect, and the most widely used was to indicate addition in each headline news. Moreover, the reasons for using transition signals in headline news were 1) to make the movement of the paragraphs in the text logical and smooth, 2) to strengthen the internal cohesion and coherence in a text, 3) to show the relationship between the parts of sentences in a paragraph or between paragraphs, and 4) to provide valuable signals to the reader about the relationship between parts of the text.